PERBEDAAN KUALITAS AIR SUMUR GALI DAN SUMUR BOR PERUMAHAN GRIYA CAHAYA 2 GUNUNG SARIAK KOTA PADANG - 147-154 . Ildayat Doni Afrizal (Universitas Negeri Padang, 2013)
147 The phenomena in field shows that the distance between pit and septic-tank is not qualified, generally septic-tank is simple constructed; leak of septic-tank’s water resulted in contamination of fresh water. Purposes of this research are to: (1) find out physical parameter of pit’s water, (2) find out microbiology parameter of pit’s water, and (3) find out chemical parameter of pit’s water. The type of this research is field and laboratorium research, which is located in Griya Cahaya 2 Gunung Sariak Residence district of Kuranji Padang. Populations in this research are 86 pits/wells and samples are 10 of pit’s water. Samples are collected by systematic sampling method by making grid system that modified based on initial-maps in this research. Data collection method is gathered from literature, observation, interview, and sampling. Physical, microbiology and chemical testing results are compared to Regulation of Health Ministry number 429/Menkes/Per/IV/2010. Results show that testing outcomes of pit-dig’s water quality compared to pit-drill’s water quality prove that pit-digs water quality is more contaminated that pit-drill’s water quality. Key words : Housing, wells, water quality